What is the role of social media? Self-Mediation, Banksy and the resistance - Wei Ling Nien (International Telecommunications Society (ITS), 2018)
This paper underlines social media enterprise graffiti arts, through self-mediation to transform the meaning of popular culture. Methodology applied together semiology and literature review. In order to understand the logic of social media that the mediation opportunity structure, methodology is focused on the way of analysing images by Roland Barthes. The project includes Banksy's graffiti that represents anti-war. The result shows that the graffiti represents the meaning of popular culture, it has to be involved in social system (e.g. the formation of graffiti, political concepts, and anti-war) through self-mediation representing popular culture, and the importance of social media on the role of discursive public sphere. We cannot ignore the logic of self-mediation where it creates a field of opportunities for discursive identity. At the same time, pro and cons for social media should also be taken into account.
Keywords: 330; self-mediation; social media; semiology